Angola Janga: critical circulation of a history of recognition (RuMoRes, 2023)
This study aims to discuss the policy of recognition in the critical circulation of Angola Janga – Uma História de Palmares (2018). This study explores the repercussions around the work in comic book form that portrays the resistance of enslaved populations in the reconstitution of the history of Quilombo dos Palmares. By making a foray into the past and proposing a narrative of the leading role of Black people, the publication is considered as having a critical attitude as it emerges at a time when the racist discourse cradles the rise of extreme right-wing forces. The reception and circulation of comics will be guided by this recognition policy not only because this is its author’s explicit intention, but also because of the importance the theme has acquired in Brazil in recent years.